Museums, Collections and Cabinets: 'Shelf after Shelf after Shelf'. - Lara-Rallo, Carmen (Peter Lang, 2009)
This chapter offers an interdisciplinary analysis of A.S. Byatt’s production from the perspective of museum studies, with the goal of discovering the recurrent presence of museums, collections, and collectors in her works. Apart from addressing Byatt’s attention to museums in her critical texts, the chapter examines Byatt’s fiction, from her early novels to her last collection of short stories, _Little Black Book of Stories_ (2003), tracing her literary treatment of the art of collecting, sorting, and exhibiting. The chapter is structured in three main sections: the first one analyses the presence of fictional and real-life museums in Byatt’s critical and narrative texts; the second one explores the figure of the collector in her novels and short stories, and the final section investigates the representation of the cabinet of curiosities in _Possession_ (1990).
Política de acceso abierto tomada de: https://new.peterlang.com/repository-policy/
Keywords: Museos - En la literatura; Exposiciones; Museos - Colecciones; Museum; Collection; Collector; Cabinet; Exhibition; A.S. Byatt; Contemporary fiction; Museum studies